A Database of Snow on Sea Ice in the Central Arctic Collected during the MOSAiC expedition - Macfarlane, Amy R.; Schneebeli, Martin; Dadic, Ruzica; Tavri, Aikaterini; Immerz, Antonia; Polashenski, Chris; Krampe, Daniela; Clemens-Sewall, David; Wagner, David N.; Perovich, Donald K.; Henna-Reetta, Hannula; Raphael, Ian; et al. (Nature Publishing Group, 2023)
Snow plays an essential role in the Arctic as the interface between the sea ice and the atmosphere. Optical properties, thermal conductivity and mass distribution are critical to understanding the complex Arctic sea ice system’s energy balance and mass distribution. By conducting measurements from October 2019 to September 2020 on the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition, we have produced a dataset capturing the year-long evolution of the physical properties of the snow and surface scattering layer, a highly porous surface layer on Arctic sea ice that evolves due to preferential melt at the ice grain boundaries. The dataset includes measurements of snow during MOSAiC. Measurements included profles of depth, density, temperature, snow water equivalent, penetration resistance, stable water isotope, salinity and microcomputer tomography samples. Most snowpit sites were visited and measured weekly to capture the temporal evolution of the physical properties of snow. The compiled dataset includes 576 snowpits and describes snow conditions during the MOSAiC expedition.